Sosialisasi Pencegahan Stunting di Kampung Reremal Melalui Rumusan Kebijakan Publik - Ashwad, Hajar; Rizki, Syahriandi; Selfirah, Nadia; Destriyadani, Rika; Alwi, Haldan; Yanti, Mira; Yani, Ulfa; Fiqih, Fiqih; Suci, Rosnatun; Halil, Munawar; Ramadhan, Sarial; Ilyas, Ilyas; Nurbaiti, Saniya; Rahmah, Jamilatu; Ramadhan, Syahru; Junaida, Muvira; Akbar, Faisal (Jurnal Pengabdian Pada Masyarakat Indonesia, 2023)
Stunting is a condition that disrupts the growth of children under the age of five. Stunting can be caused by factors such as the phase of pregnancy, unmet nutritional needs, and the child's health condition. Based on the nutritional status survey of the Indonesian Minister of Health in 2022, the prevalence of stunting in toddlers is 21.6%. The government targets reducing the prevalence of stunting to 14% by 2025 by involving various parties in efforts to reduce the prevalence of stunting. Students carry out community service by implementing the knowledge they have in their scientific field. The method used to achieve the objectives in this service is carried out through stages: document review, focus group discussions, interviews, submission of policy recommendation documents, and socialization. This service concludes that the aim of the service was achieved, namely providing policy recommendations and also conducting socialization. as a form of application of student knowledge in preventing stunting cases in Reremal village.